2017
DOI: 10.1007/978-3-319-51753-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Approximation Algorithms for Computing Maximin Share Allocations

Abstract: We study the problem of computing maximin share guarantees, a recently introduced fairness notion. Given a set of n agents and a set of goods, the maximin share of a single agent is the best that she can guarantee to herself, if she would be allowed to partition the goods in any way she prefers, into n bundles, and then receive her least desirable bundle. The objective then in our problem is to find a partition, so that each agent is guaranteed her maximin share. In settings with indivisible goods, such alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
173
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(178 citation statements)
references
References 17 publications
(14 reference statements)
5
173
0
Order By: Relevance
“…This fact initiated research on approximate MMS allocations of goods in which each agents gets some fraction of her MMS guarantee [18]. There have been several works on algorithms that find an approximate MMS allocation [19][20][21][22][23]. [7] showed that although an MMS allocation of goods may not always exist, but there exists a polynomial-time algorithm that returns a 2 3 -approximate MMS allocation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact initiated research on approximate MMS allocations of goods in which each agents gets some fraction of her MMS guarantee [18]. There have been several works on algorithms that find an approximate MMS allocation [19][20][21][22][23]. [7] showed that although an MMS allocation of goods may not always exist, but there exists a polynomial-time algorithm that returns a 2 3 -approximate MMS allocation.…”
Section: Related Workmentioning
confidence: 99%
“…Algorithms for computing approximate MMS allocations of goods are being used in practice for fair division in real-world problems [24]. The authors of [19][20][21] proposed an algorithm that can guarantee an approximate MMS allocation. The work mentioned above only focused on the case of goods.…”
Section: Related Workmentioning
confidence: 99%
“…Harsanyi (1975) argued in favor of expected utilitarianism, loosely the maxsum principle, except in cases where the maximin choice was similar to the maxsum choice, as in the case in our experiments. There has been a strong focus on maximin mathematically and in economics (e.g., Amanatidis, Markakis, Nikzad, & Saberi, 2017; Barman & Krishna Murthy, 2017; Dubois, Fargier, & Prade, 1996; Escoffier, Gourvès, & Monnot, 2013; Kurokawa, Procaccia, & Wang, 2016; Procaccia & Wang, 2014), including applications to networking (e.g., bandwidth‐sharing) (Salles & Barria, 2008). Choices aligned with the maximin , maxsum metric, and IA metrics are often compared in studies, and results are often mixed, with participants trading off between different metrics depending on the numbers and contexts involved (Ahlert, Funke, & Schwettmann, 2013; Charness & Rabin, 2002; Engelmann & Strobel, 2004; Faravelli, 2007; Fehr et al, 2006; Gaertner et al, 2001; Gaertner & Schwettmann, 2007; Konow, 2001, 2003; Konow & Schwettmann, 2016; Mitchell, Tetlock, Mellers, & Ordonez, 1993; Ordoñez & Mellers, 1993; Pelligra & Stanca, 2013; Schwettmann, 2009, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of fair allocation of indivisible goods has recently garnered a lot of interest (Amanatidis, Birmpas, and Markakis 2018;Barman et al 2018;Endriss 2017;Brandt et al 2016;Amanatidis et al 2015;Bouveret and Lemaître 2014;Procaccia and Wang 2014;Kurokawa, Procaccia, and Wang 2016). Several important practical problems-for eg., matching courses, resolving inheritance issues, allocating cloud computing resources-naturally lend themselves to the problem of assigning goods to agents, when the goods cannot be fractionally allocated.…”
Section: Introductionmentioning
confidence: 99%